A protocol to study the effect of targeted parental education intervention to identify early childhood development disorder – multisite interventional study - Vadivelan Kanniappan; Prakash Muthuperumal; P. Venkataraman; Anuradha Murugesan; Balaji Chinnasami; Manikumar Muthiah; Subramanian Sethuraman; Abishek J. R.; Shrisruthi Suresh; Murali Krishnan Nambirajan; Angeline Grace G.; Veeragoudhaman T. S.; et al. (Archives of Public Health)
Abstract Background In India, approximately 3.5 million children are affected by Developmental Delay (DD), often stemming from preterm births. These delays contribute to neurological and motor development delays, placing a significant financial burden on families. Maternal unemployment rates are also elevated in such cases. Delayed Developmental Milestones identification, often due to a lack of parental awareness, further compounds these challenges. This study introduces a multiphasic approach aimed at educating antenatal women on monitoring neurological maturation, with the overarching objective of assessing the effectiveness of a targeted multi-method parental education intervention in improving parents’ knowledge and early detection of developmental disorders in early childhood. Methods Antenatal women will be assigned to intervention or control groups. The intervention group will undergo specialized training in a multiphasic study, while the control group will receive routine care. A meticulously developed intervention module for early detection of neurodevelopmental disorders will empower mothers to monitor their newborns for potential deficits. Outcomes will be assessed through questionnaires, analyzing knowledge improvement and early identification of DD using statistical methods such as chi-square tests. The study involves three phases: preparatory, implementation, and evaluation, aiming to empower mothers to detect developmental concerns early and improve maternal awareness of child development. The study was approved by the SRM Institutional Ethical Committee with the reference number 8688/IEC/2023. Discussion This study will identify DD and improve parental awareness by providing tools for early detection thereby empowers parents to identify developmental concerns early. The study supports policy goals to reduce the burden of DD, enhance early intervention, and improve long-term outcomes for children. It is anticipated that this intervention will complement existing health policies, contributing to better child health and developmental outcomes in India. Trial registration Trail is registered under Clinical Trails Registry - India (CTRI/2024/04/065008) registered on 01 April 2024.